Usefulness of thresholds for smear review of neutropenic samples analyzed with a Sysmex XN-10 analyzer. (18th August 2017) - Ronez, Emily; Geara, Carole; Coito, Sylvie; Jacqmin, Hugues; Cornet, Edouard; Troussard, Xavier; Chatelain, Bernard; Mullier, François
Abstract: Neutropenia is one of the main criteria for a blood smear review. The objective of this study was to compare the thresholds proposed by the international consensus group for hematology review (1.0 10 9 /L) and the French speaking Group for Cellular Haematology (1.5 10 9 /L) in terms of the number of useless smears. We collected 112, 097 analyzed samples from four laboratories equipped with XN instruments (Sysmex, Kobe, Japan) during early 2016. The only exclusion criterion was a leucocyte count below 0.5 10 9 /L. In the absence of abnormal cells and/or morphology suggesting haematological disease, samples were classified as 'negative for morphology' and the differential from the XN-10 was reported. These smear procedures were considered as uninformative. Some 2202 samples met the criterion for neutropenia (<1.5 10 9 /L) for slide review representing 1.96% of the total. These included 1031 with neutropenia alone and 1171 neutropenia plus other abnormalities. Of the 1031 with neutropenia alone, 886 had a neutrophil count between 1.0 10 9 /L and 1.5 10 9 /L. The smear was uninformative for all of these samples. In conclusion, microscopic examination of a blood smear provided very limited information in cases of neutropenia without other abnormalities.